Environmentalism Reflected At Henrik Ibsen's Public Enemy(1882): A Sociological Approach - Jafar, Muhamad; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2015)
The research is proposed to analyze the social aspects in A Public Enemy. The major problem in this article is to explain how the social problem reflected in A Public Enemy. The object of the study is An Enemy of the People drama written by Henrik Ibsen. Qualitative study is a method which is used to analyze the sociological aspects reflected in the drama. The result of this study is Henrik Ibsen shows the social condition of Norway. Although Norway in nineteenth century was including progresive country, Henrik Ibsen also criticized the goverment for controlling the society and ruling as the majority to the minority.